Transnasal Humidified Rapid Insufflation Ventilatory Exchange With Nasopharyngeal Airway Facilitates Apneic Oxygenation: A Randomized Clinical Noninferiority Trial - Chen, Lingke; Yang, Liu; Tian, Weitian; Zhang, Xiao; Zhao, Yanhua; Huang, Lili; Tian, Jie; Zhang, Jiaqiang; Wu, Jiangxia; Yu, Weifeng; Su, Diansan (Frontiers in Medicine, 2020)
Background: Transnasal humidified rapid insufflation ventilatory exchange (THRIVE) was used to extend the safe apnea time. However, THRIVE is only effective in patients with airway opening. Nasopharyngeal airway (NPA) is a simple device that can help to keep airway opening. This study aimed to investigate the noninferiority of NPA to jaw thrust for airway opening during anesthesia-induced apnea. Methods: This was a prospective randomized single-blinded noninferiority clinical trial on the use of THRIVE in patients with anesthesia-induced apnea. Participants were randomly allocated to receive NPA or jaw thrust. The primary outcomes were PaO2 and PaCO2 at 20 minutes after apnea, with noninferiority margin criteria of −6.67 and 0.67 kPa, respectively. Results: A total of 123 patients completed the trial: 61 in the NPA group and 62 in the jaw thrust group. PaO2 at 20 min after apnea was 42.9 ± 14.0 kPa in the NPA group and 42.7 ± 13.6 kPa in the jaw thrust group. The difference between these two means was 0.25 kPa (95% CI, −3.87–4.37 kPa). Since the lower boundary of the 95% CI was >−6.67 kPa, noninferiority was established because higher PO2 is better. PaCO2 at 20 min after apnea was 10.74 ± 1.09 kPa in the NPA group and 10.54 ± 1.18 kPa in the jaw thrust group. The difference between the two means was 0.19 kPa (95% CI, −0.14 to 0.53 kPa). Since the upper boundary of the 95% CI was <0.67 kPa, noninferiority was established because lower PCO2 is better. No patient had a SpO2 <90% during apnea. Conclusion: When THRIVE was applied during anesthesia-induced apnea, NPA placement kept airway opening and was noninferior to jaw thrust in terms of its effects on PaO2 and PaCO2 at 20 minutes after apnea. Clinical trial registration: ClinicalTrials.gov (NCT03741998)